Analisis Strategi Pelayanan Jemaah Umrah dalam Meningkatkan Brand Image pada Travel PT. Bimalyndo Hajar Aswad Cabang Bukittinggi - Mardatillah Hutabarat; Yuwarman Mansur (ARZUSIN, 2026)
Service strategies for Umrah pilgrims in improving brand image have become a focus in various previous studies; however, research that specifically discusses the comprehensive implementation of service strategies at the operational level of travel agencies, particularly in the context of a decline in the number of pilgrims, remains limited. This study aims to analyze service strategies for Umrah pilgrims in improving brand image at PT Bimalyndo Hajar Aswad, Bukittinggi Branch. This study employed a qualitative approach with a field research design. The research informants consisted of the branch manager, employees, and pilgrims selected through the purposive sampling technique. Data were collected through observation, in-depth interviews, and documentation and were then analyzed using interactive analysis techniques, including data reduction, data presentation, and conclusion drawing. The results show that the service strategy has covered the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, but its implementation has not been fully optimal, particularly in terms of transportation facilities to the airport and service consistency. These findings contribute to the development of studies on service quality and brand image, as well as broaden understanding of service strategies in the Umrah travel industry. The conclusion of the study emphasizes that service quality and consistency play an important role in shaping the company’s image. The practical implication is that the travel agency needs to improve its facilities and overall service quality to strengthen trust, satisfaction, and a positive image among pilgrims.